Pengaruh Pembelajaran Daring Masa Pandemi Covid-19 terhadap Motivasi Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam - Kholifatul Azizah; Ahmad Haromaini; Sugih Suryagalih (Qiro'ah : Jurnal Pendidikan Agama Islam, 2021)
This research was conducted with the aim to be achieved, namely to find out how much influence online learning has on the learning motivation of 8th and 9th grade students in Islamic religious education subjects at SMP Plus Al-Ijtihad 2 Kutabaru, Pasar Kemis Subdistrict, Tangerang Regency. The research method used is a descriptive method with a quantitative approach. A method that describes a phenomenon in the field with a data analysis approach. The instrument in this study is to use a questionnaire (questionnaire) and interviews as a source of data. And the sample used in the study used systematic random sampling. Respondents of this study amounted to 54 students. Based on the results of data processing and discussion that the effect of online learning on the motivation of students in Islamic religious education subjects can be proven by calculating the Product Moment correlation, the result is 0.557. In variable X online learning during the Covid-19 pandemic and variable Y student learning motivation in the PAI folder, there is an influence between variables X and Y, the correlation is moderate/sufficient in the coefficient interval 0.40-0.599. So it can be concluded that the effect of online learning on students' learning motivation in PAI subjects is 31.0% and the remaining 69.0% is influenced by other factors which may be family environment factors, the environment between friends and so on.